(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the periodization of the basic areas of research in the field of artificial intelligence. The first examples of systems created to perform intellectual tasks are considered in detail. The significance of experimental work for the subsequent creation of intelligent machines is described